2022
DOI: 10.1177/00219983221075418
|View full text |Cite
|
Sign up to set email alerts
|

A hydrophobic coating on cellulose nanocrystals improves the mechanical properties of polyamide-6 nanocomposites

Abstract: Recent demands for high-performance lightweight materials have brought researchers’ attention to various nanoparticles to reinforce polymeric materials. As such, sustainable and stiff cellulose nanocrystals (CNC) have become a popular candidate as nano-reinforcements. While CNC can offer great advantages, such as high mechanical properties and low density, it might agglomerate even in hydrophilic polymers because of its strong affinity to itself (intra and intermolecular hydrogen bonds) which prevents its broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Formic acid, CH2O2 (98%+ pure), was obtained from ACROS Organics and used in liquid form. Many studies have reported that formic acid has a corrosive effect on polyamide [21]. For this reason, it is preferred for surface modification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formic acid, CH2O2 (98%+ pure), was obtained from ACROS Organics and used in liquid form. Many studies have reported that formic acid has a corrosive effect on polyamide [21]. For this reason, it is preferred for surface modification.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the printing direction on the surface roughness for flat samples was examined on the X-Y plane, and for on-edge samples, the effect of layer thickness was examined on the Z-axis. 239 literature knowledge literature [24][25][26][27], formic acid was preferred, and these stated processing values were selected in this study because it was observed to have a corrosive effect on polyamide material.…”
Section: Production Of Test Samplesmentioning
confidence: 99%
“…When the SA content is high, some SA molecules will be excluded to the interface between PA6 and BN, leading to the improvement of the compatibility between PA6 and BN. Therefore, SA was often used in PA6 composites to promote the compatibility between PA6 and fillers [44]. In this work, when the SA content is less than 3 phr, it is mainly distributed in the PA6 phase.…”
Section: Morphologymentioning
confidence: 99%